Antimicrobial activity of amurca (olive oil lees) extract against selected foodborne pathogens - Janakat,Sana (2015)
The antimicrobial activity of a methanolic extract of amurca (olive oil lees) was determined against both Gram-positive (L. monocytogenes and S. aureus) and Gram-negative (E. coli O157:H7 and S. enteritidis) foodborne pathogens at 10 °C or 37 °C using microdilution and disk diffusion methods, and its relative activity was compared to selected antibiotics. Minimum inhibitory (MIC) and minimum bactericidal (MBC) concentrations of amurca extract ranged from 60 to 80 µl/ml at 37 °C after 24 h against all tested strains. At 10 °C, amurca was more inhibitory with MIC and MBC values of 40 and 60 µl/ml, respectively, after 7 d against tested strains. Amurca at 40 µl/ml reduced numbers of tested pathogens by 2.5 to 3.2 log10 CFU/ml at 10 °C after 7 d, but was not inhibitory at 37 °C after 24 h. Protein prepared from amurca was not antimicrobial. The relative antimicrobial activity (inhibition zone ratio) of 80 µl/ml amurca methanolic extract compared to chloramphenicol, erythromycin, gentamycin and tetracycline ranged from 0.36 to 1.0 against Gram-negative and from 0.45 to 2.0 against Gram-positive bacteria. In addition, amurca extract inhibited E. coli O157:H7 02-0628 and S. aureus 26127 which were resistant to tetracycline and chloramphenicol, respectively.